The Factors Contributing to a Corporation's Demise: An Analysis of Enron - Dr. Muhammad Asif Khan; Umar Niaz Khan; Aamir Khan Jamali; Jibran Jamshed (Journal of Management Practices, Humanities and Social Sciences, 2022)
That the very first decade of the twenty - first century has already seen significant reforms in the major business organisations. The Surbanes Oxley Act 2002 in the United States and the Higgs and Smith reports (2003) in the United Kingdom have both introduced significant improvements to the world's two most important business systems (Sarbanes-Oxley Act, 2002). These changes were implemented as a result of large company failures such as those experienced by Enron, WorldCom, Adelphia, Global Crossing, K. Mart, and Parmalat. Among these corporate failures, Enron is widely considered to be the worst catastrophe in the history of business. This article investigates the factors that contribute to a company's demise and points out any inconsistencies that may exist. The impact from the Enron scandal is used to illustrate the concept of a business collapse.